Public-Private Collaboration for Export Success - International Trade Centre (United Nations, 2012)
This publication compiles case studies for business leaders, policymakers and development practitioners, showcasing successful experiences of public-private dialogue in developing countries. It outlines activities driven by the governments and targeted at private sector players in the form of public-private partnerships for service delivery and public-private consultative bodies. It also presents private sector initiatives targeted at public sector players in the form of business advocacy, and it demonstrates the essential role of the private sector in trade and development through examples featuring the Barbadian tourism industry, customs services in Ghana, Thailand’s automotive industry, Penang’s export hub for electronics, and India’s textile parks.